Respostas
respondido por:
259
15+[(3x6-2)-(10-6:2)+1]=15 + [(18-2) - (10 -3) +1] =
15 + [16 - 7 +1] =
15 +[9 + 1 ] =
15 + 10 =
25
15 + [16 - 7 +1] =
15 +[9 + 1 ] =
15 + 10 =
25
respondido por:
202
15+[(3x6-2)-(10-6:2)+1]=
15+[(18-2)-(10-3)+1]=
15+[18-2 - 7 +1]=
15+[18-9+1]=
15+ 18-8=
33-8=
25
15+[(18-2)-(10-3)+1]=
15+[18-2 - 7 +1]=
15+[18-9+1]=
15+ 18-8=
33-8=
25
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
= 15+[(18-2)-(10-3)+1]=
=15+[16-7+1]=
=15+[9+1]=
=15+10=
=25